2018
DOI: 10.1016/s1474-4422(18)30195-9
|View full text |Cite
|
Sign up to set email alerts
|

Restenosis and risk of stroke after stenting or endarterectomy for symptomatic carotid stenosis in the International Carotid Stenting Study (ICSS): secondary analysis of a randomised trial

Abstract: SummaryBackgroundThe risk of stroke associated with carotid artery restenosis after stenting or endarterectomy is unclear. We aimed to compare the long-term risk of restenosis after these treatments and to investigate if restenosis causes stroke in a secondary analysis of the International Carotid Stenting Study (ICSS).MethodsICSS is a parallel-group randomised trial at 50 tertiary care centres in Europe, Australia, New Zealand, and Canada. Patients aged 40 years or older with symptomatic carotid stenosis meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 25 publications
2
90
1
2
Order By: Relevance
“…17 The PSV ICA cut-off values used to quantify the severity of stenosis were >1.3 m/s for ≥50% stenosis, and > 2.1 m/s for ≥70% stenosis, but the EDV ICA and the PSV ICA/PSV CCA ratio were also considered ( Table 2). 8,18 No correction was made for the presence of a stent or stent design when measuring stenosis. 8 Ultrasound velocity measurements were not available from a small number of centres; in these cases, the percent stenosis reported by the local ultrasonographer and investigator was used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The PSV ICA cut-off values used to quantify the severity of stenosis were >1.3 m/s for ≥50% stenosis, and > 2.1 m/s for ≥70% stenosis, but the EDV ICA and the PSV ICA/PSV CCA ratio were also considered ( Table 2). 8,18 No correction was made for the presence of a stent or stent design when measuring stenosis. 8 Ultrasound velocity measurements were not available from a small number of centres; in these cases, the percent stenosis reported by the local ultrasonographer and investigator was used.…”
Section: Discussionmentioning
confidence: 99%
“…8,18 No correction was made for the presence of a stent or stent design when measuring stenosis. 8 Ultrasound velocity measurements were not available from a small number of centres; in these cases, the percent stenosis reported by the local ultrasonographer and investigator was used. For the purpose of this study, moderate or higher restenosis was defined as ≥50% stenosis or occlusion of the treated carotid artery seen at any time during follow-up after completion of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this study is a transient case, WSS was time averaged to get the mean value representing WSS for each cardiac cycle of heartbeat. Thus, TAWSS was calculated using equation (2) where T is the duration of one cardiac cycle and dt is the increment of time [28]. Therefore, TAWSS based on research by Malek et al (1999) was split into three variables, which are TAWSShigh, TAWSSnorm and TAWSSlow [16].…”
Section: Haemodynamic Parameters Of Stented Carotid Arterymentioning
confidence: 99%
“…However, re-blockage or restenosis of the artery tend to happen again after 30 days of stent implantation where the reported cause of the complication is due to the geometrical stent strut configuration [1]. Within five years after stent implantation, a moderate restenosis with 50% of an arterial diameter reduced is reported to have *Corresponding author: iszat@uthm.edu.my an occurrence rate about 40.7% while a severe restenosis with 70% of the arterial diameter reduced has an occurrence rate about 10.6% [2]. Kastrati et al found that stent design is among the strongest factors of restenosis incidence ranging from 20.0% to 50.3% [3].…”
Section: Introductionmentioning
confidence: 99%